MOOC teaching assistants’ global-engaged learning in the US and China - Li, Yue; Armstrong, Anne; Krasny, Marianne (Online Learning, 2024)
How can we create a “global-at-home” learning experience for university students to engage them in serving global professional communities online? This study applied global engagement surveys alongside interviews and focus groups in online contexts to examine engaged learning outcomes of US and Chinese university students who served as MOOC teaching assistants to interact with the course participants from over 50 countries. Findings from pre and post surveys showed that TAs significantly increased their scores on efficacy, political voice, conscious consumption and critical reflection. Further, qualitative analysis showed that TAs worked to adapt their language in their communication with participants, a key aspect of intercultural competence, and that they gained self-efficacy in online communication and in their ability to make a difference. TAs described affordances of online global-engaged learning, including accessibility, time for reflection, lack of implicit bias, creating long-term connections, and reaching large audiences. They also reflected on challenges, including lack of emotional connection, lack of response from participants, language barriers, and perceived lack of expertise. The study offers recommendations for designing online learning and community engagement experiences that can provide opportunities for university students to gain intercultural competence, efficacy, and reflection.